2010
DOI: 10.1021/ac102301j
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Currently Marketed Heparin Products: Reversed-Phase Ion-Pairing Liquid Chromatography Mass Spectrometry of Heparin Digests

Abstract: Here we report results from the analyses by enzymatic digestion and reversed-phase ion-pairing liquid chromatography mass spectrometry (RPIP-LC-MS) of active pharmaceutical ingredient (API) unfractionated heparins (UFHs) from six different manufacturers and one USP standard sample. We employed a reverse phase ion-pairing chromatography method using a C(18) column and hexylamine as the ion-pairing reagent with acetonitrile gradient elution to separate disaccharides generated from the digestion of the heparins b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 31 publications
3
49
1
Order By: Relevance
“…All the disaccharides, including II-H/III-H and II-S/III-S which were not resolved by RPIP-HPLC in our previous work [26], were either separated by UHPLC chromatography or by exact mass in extracted ion chromatograms. The split peaks observed for IV-A and III-S are attributed to resolved ␣-and ␤-anomers [33] (Fig.…”
Section: Separation Of Heparin Disaccharides By Rpip-uhplcmentioning
confidence: 95%
See 4 more Smart Citations
“…All the disaccharides, including II-H/III-H and II-S/III-S which were not resolved by RPIP-HPLC in our previous work [26], were either separated by UHPLC chromatography or by exact mass in extracted ion chromatograms. The split peaks observed for IV-A and III-S are attributed to resolved ␣-and ␤-anomers [33] (Fig.…”
Section: Separation Of Heparin Disaccharides By Rpip-uhplcmentioning
confidence: 95%
“…For example, our laboratory reported conditions where the combined use of relatively high amounts heparin lyase I and III were effective for complete digestion of heparin sodium [26]. By contrast, Xiao et al observed that heparin lyase II yielded more efficient digestion than treatment with heparin lyase I or III alone and that applying lyase III alone did not provide efficient heparin digestion [9].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations